Safety of azithromycin in infants under six months of age in Niger: A community randomized trial - Oldenburg, Catherine E.; Arzika, Ahmed M.; Maliki, Ramatou; Kane, Mohamed Salissou; Lebas, Elodie; Ray, Kathryn J.; Cook, Catherine; Cotter, Sun Y.; Zhou, Zhaoxia; West, Sheila K.; Bailey, Robin; Porco, Travis C.; et al. (PLOS Neglected Tropical Diseases, 2018)
Author summary Trachoma control programs currently treat all adults and children age 6 months and older in communities endemic for trachoma. If shown to be safe, programs could consider inclusion of younger children in mass treatment programs. Here, we evaluated adverse events in infants aged 1–5 months who were participating in a placebo-controlled trial of mass azithromycin for the reduction of child mortality in Niger. Overall, there was no difference in the frequency of adverse events among children treated with azithromycin compared to placebo. Common adverse events in both arms included diarrhea, vomiting, and skin rash. Azithromycin distribution to children between 1 and 5 months of age appeared to be safe. Inclusion of younger children in azithromycin-based trachoma and child mortality programs could be considered.